Repositioning Quinacrine Toward Treatment of Ovarian Cancer by Rational Combination With TRAIL - Liang, Rui; Yao, Yuanfei; Wang, Guangyu; Yue, Er; Yang, Guangchao; Qi, Xiuying; Wang, Yang; Zhao, Ling; Zheng, Tongsen; Zhang, Yanqiao; Wenge Wang, Edward (Frontiers in Oncology, 2020)
Quinacrine has been identified as a potent DR5-inducing agent that sensitizes cancer cells to TRAIL-induced apoptosis. In the current study, we found that quinacrine induced significant DR5 mRNA level in ovarian cancer cell line regardless of p53 status. Further study showed half-life of DR5 in quinacrine-treated cells was also significantly prolonged, indicating that DR5 protein degradation was blocked by quinacrine. We tested the combination of TRAIL and quinacrine in ovarian cancer cell lines and in ovarian cancer xenograft mice to determine if this combination could be effective in ovarian cancer treatment. We found that quinacrine enhanced TRAIL sensitivity or reversed TRAIL resistance in all the ovarian cancer cell lines tested. Mice treated with quinacrine and TRAIL remain disease-free up to 18 weeks; however, all mice in the control group, TRAIL alone, or quinacrine alone group, died within approximately 8 weeks after treatment. Intraperitoneal delivery of quinacrine and TRAIL is rational and practical with extraordinary synergistic anti-cancer effects in preclinical models of ovarian cancer. Clinical investigation of repositioning quinacrine in combination with TRAIL for ovarian cancer treatment is warranted.